Project Planning & Scheduling: بحث تطبيقي لمشاريع / مديرية الابنية المدرسية /دائرة المشاريع /مشروعالوزارةرقم (1) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
Construction project life-cycle processes must be managed in a more effective and predictable way to meet project stakeholder needs , However, there is increasing concern about whether know-how effectively improves  understanding of underlying theories of project management processes for construction organizations and their project managers  Project planning and scheduling are considered as key and challenging tools in controlling and monitoring project performance , but many worldwide construction projects appear to give insufficient attention to effective management and definition of  project  planning, including pre planning stages . Indeed, some planning issues indeed, some planning issues have been completely overlooked, resulting in unsatisfactory project performance. There is a lack of knowledge of, and understanding about, the significance of applications of project planning and scheduling theory in construction projects.Thus, improving such knowledge should be incorporated with new management strategies or tools to improve organizational learning and integration in the context of project planning and scheduling.This implies a need to assess project stakeholders’ understanding on the application of project planning and scheduling theories to practice.